Manusia Pertama Itu Namanya Ina: Membaca Narasi Mitos Penciptaan dari Perspektif Perempuan Maluku - Weldemina Yudit Tiwery (Indonesian Journal of Theology, 2017)
This article elucidates the concept of creation, which is examined through the narrative of the creation of the Moluccas and the first Moluccans. As with Hebrew, Babylonian or Greek mythological tradition, the Moluccans also maintain a historical narration of the creation myth. This myth within the Moluccan tradition begs to be interpreted. The Moluccas (Nusaina) are considered by Moluccans to be a home shared as fellow brothers (and sisters), emerging from one womb of Ina (mother) who inhabits the realm of Nusaina. This creation narrative focuses on the role of Ina or mother as the central figure. Ina is she who is pregnant, breastfeeding, nurturing and raising. Beyond myth, this narrative also contains theological value, which needs to be constructed to offer theological meaning for the people of the Moluccas.